Association between suicide risk and traumatic brain injury in adults: a population based cohort study. Issue 1142 (3rd February 2020) - Lu, Yueh-Chien; Wu, Ming-Kung; Zhang, Li; Zhang, Cong-Liang; Lu, Ying-Yi; Wu, Chieh-Hsin
Abstract: Background: Traumatic brain injury (TBI) is a major cause of death and disability worldwide, and its treatment is potentially a heavy economic burden. Suicide is another global public health problem and the second leading cause of death in young adults. Patients with TBI are known to have higher than normal rates of non-fatal deliberate self-harm, suicide and all-cause mortality. The aim of this study was to explore the association between TBI and suicide risk in a Chinese cohort. Method: This study analysed data contained in the Taiwan National Health Insurance Research Database for 17 504 subjects with TBI and for 70 016 subjects without TBI matched for age and gender at a ratio of 1 to 4. Cox proportional hazard regression analysis was used to estimate subsequent suicide attempts in the TBI group. Probability of attempted suicide was determined by Kaplan-Meier method. Results: The overall risk of suicide attempts was 2.23 times higher in the TBI group compared with the non-TBI group (0.98 vs 0.29 per 1000 person-years, respectively) after adjustment for covariates. Regardless of gender, age or comorbidity, the TBI group tended to have more suicide attempts, and the risk attempted suicide increased with the severity of TBI. Depression and alcohol attributed disease also increased the risk of attempted suicide in the TBI group. Conclusion: Suicide is preventable if risk factors are recognised. Hence, TBI patients require special attention to minimise their risk of attempted suicide.